Dano moral: da natureza da indenização aos critérios para fixação do Quantum - Peres, Célia Mara (2006)
The present dissertation turns on punitive damages, the nature that they assume in the Brazilian legal system and the problematic around the quantum that must be awarded to the victim. This work intends to demonstrate the importance assumed by the study of the punitive damages in the national and world-wide scene, once the practice of this illegal conduct confronts the constitutional principle that guarantees the respect of the dignity of the human being, by violating the rights of the personality. Still, it tries to detach the difficulties to find an ideal way to award the victim the fairest relief, which is generally pecuniary, without compromising the legal relationship balance. In order to make some considerations about the subject proposed, it was necessary to make a previous study about the civil liability, by dealing with its evolution and principles and focusing on the different aspects around the punitive damages, such as the concept, indemnity, doctrines, trajectory of the former court decisions and the recognition of the man as the centre of the legal system, relegating the patrimony to a second plan. The compilation method was used during the development of this study, also the research of jurisprudence and comparative legislation. Laws and projects of law which are in transaction process had been mentioned as well. From this study, we can infer that instead of applying tax rates, the legal arbitration continues to be the best way to award the damage, since the magistrates observe the real necessity of basing their decisions and discriminating, in a individualized way, each of the judgments already consecrated by the doctrine and the jurisprudence, and mainly, the reasons that took them into that conclusion